PAKET TEKNOLOGI PENGOLAHAN AIR LIMBAH RUMAH SAKIT YANG MURAH DAN EFISIEN - Said, Nusa Idaman (Jurnal Air Indonesia, 2006)
Wastewater coming from hospital represents one of the very potential sources of water contamination. This matter is caused by hospital wastewater contanined a lot of organic compound, and of other chemical compounds, and also patogen microorganism which able to cause disease to society. Because of potential impact of hospital waste to health of society is very big, hence hospital wastewater have to process until fulfill conditions according to effluent standard. One of the alternatives to overcome the problem is by using technology processing of wastewater with process of biofilter anerob-aerob. The anaerob-aerob biofilter process have some excellence for example its simple operation, yielded a few or little of mud, can be used for the processing of waste water with low concentration and also high concentration, hold up to fluctuation of debit or concentration, and also its cheap operating expenses. Kata kunci : Air limbah, rumah sakit, teknologi pengolahan, biofilter, anaerob-aerob.